Analyzing the Effect of Brand Preference, Brand Image, and Price toward Oppo Smartphone Purchasing Intention Among Islamic University Students - Afi Rachmat Slamet; Nur Hidayati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
As one of the brands of smartphone products, Oppo already has a good market share in the market in Indonesia and has become one of the smartphone products that are well considered and chosen by its users, including students in Islamic University. The purpose of this study was to analyze the most dominant impact between brand preference, brand image, and price on the purchase intention of Oppo Smartphones perceived by students at the Faculty of Economics and Business, Islamic University of Malang. Data collection was taken over one month period, as 97 respondents are participating in this study. The data collected was processed and analyzed quantitatively to test the effect on each relationship between variables in the research model that was built. Among the three proposed hypotheses, only two were accepted and confirmed in this study. An important finding is revealed that price is not considered an important factor in Oppo Smartphone purchase intention. Thus, the price of Oppo Smartphone descriptively is the best thing perceived by respondents. Meanwhile, brand image was found to be the most important determinant of purchase intention as perceived by respondents. Discussions and opportunities for further research are presented at the end of this study.